Development of an efficient route toward meiogynin A-inspired dual inhibitors of Bcl-xL and Mcl-1 anti-apoptotic proteins1. Issue 19 (21st May 2015) - Desrat, Sandy; Remeur, Camille; Roussi, Fanny
<x xml:space="preserve">Abstract</x> The synthesis, on a large scale, with very good yield and er via an efficient strategy, of a chiral 4-substituted 2-cyclohexenone intermediate, was a milestone in the synthesis of seven analogues of meiogynin A, a natural sesquiterpenoid dimer.